Integration of Kaizen Management and Balanced Scorecard (BSC) Models to Provide a Model for Continuous Improvement of Hospital Performance(Case Study: Hospitals of Shahroud University of Medical Sciences) - Mohammad Yahyaei; Ali Akbar Ahmadi; Pirhossein Koulivand; Mojtaba Rajab Beygi (Tehran University of Medical Sciences, 2020)
Background and Aim: In todaychr('39')s complex work environment, organizations need a strong link between strategy and effective strategy execution. The purpose of this research is to integrate Balanced Scorecard model with Kaizen management to meet this need and increase innovation efficiency in organization and create sustainable competitive advantage. Materials and Methods: This study was a descriptive study in terms of purpose and in terms of data collection, in three stages. Two researcher-made questionnaires(validity and reliability of 0.852)were used perform this applied research in Shahroud hospitals. The first is identify factors using the Delphi method by 16 experts and The second was to confirm the indices, which were completed randomly by 829 hospital beneficiaries and analyzed by confirmatory factor analysis. Structural-interpretive model was used to determine the effect of indicators on each other. In order to determine the cause and effect relationships between the goals and the two models Quality Function Deployment matrix was used by expert opinion. Results: This study showed that in order to achieve the goals of learning development perspective in BSC model, one needs to use "mura" in Kaizen model. Also, to achieve internal process goals, the muri dimension must be used, to achieve the financial perspective objectives of the "deletion"(muda), and for the customer perspective goals, the "mura" dimension must be applied. Conclusion: Integration of BSC and Kaizen models can provide a suitable framework for continuous improvement of performance, because it has been successfully Performance in Shahroud hospitals, this research has shown that it seeks continuous improvement and increased productivity in the hospital.